УМОВИ ПЕРЕЗАРЯДУ КОНДЕНСАТОРІВ КОМУТУЮЧОЇ ЛАНКИ ТРИФАЗНОГО МОСТОВОГО КОМПЕНСАЦІЙНОГО ПЕРЕТВОРЮВАЧА - Бойко, В.С.; Шкардун , О.В. (Інститут електродинаміки НАН України, Київ, 2023)
The authors have developed a three-phase bridge compensation converter circuit, in which a three-phase group of fully controlled devices plays the role of a commutative. This technical solution allows to provide a controlled recharge of the capacitors of commutating. The authors investigated the conditions for the formation of the commutating voltage, which, in shape and magnitude, is capable of providing a compensation mode of operation of power electric diodes, that is, their operation with a leading angle of regulation. At the same time, fully controlled commutating devices have a single control frequency and operate for a third of the period. It has been proven that a three-phase bridge converter is capable of operating in a compensation mode if, to recharge a capacitor battery, a group of fully controlled commutating devices is regulated within the operation of a power electric diodes of its own phase or the next phase. The method of harmonic analysis is used to compare the characteristics of the commutating voltage for different modes of its formation. Refer. 8, fig. 5, table 2.